Who occupies disability?/Quem ocupa a deficiência? - Block, Pamela; Pollard, Nick (Cadernos Brasileiros de Terapia Ocupacional, 2017)
Locating occupational therapy within gendered and racialized systems of power, the authors consider the intersectional nature of critical disability studies discourse and the need for occupational therapy to incorporate such values into practice. This article discusses ways in which occupational therapy as a profession and individual therapists can align with or resist the economic determination which has come to dominate medical systems. It considers some of the political background to the history of the profession and its relationship with power. This positioning of the profession is explored against the impact of neoliberal economic policy on health, rights, service delivery and disability, and against some key issues, the pressure of ageing populations and the positon of occupational therapists as women professionals. Current policies present a critical challenge to central occupational therapy tenets. Occupational therapists may find themselves working both in alliance with disabled people and disability activists, and against them.